Metformin improves intestinal ischemia-reperfusion injury by reducing the formation of mitochondrial associated endoplasmic reticulum membranes (MAMs) and inhibiting ferroptosis in intestinal cells - Zhao, Xu; Yan, Likun; Tian, Lifei; Zhang, Xiaolong; Liu, Ruiting; Li, Zeyu (Frontiers in Pharmacology, 2025)
IntroductionIntestinal ischemia-reperfusion (I/R) injury represents an inevitable and formidable postoperative challenge for all clinical surgeons. Ferroptosis has emerged as a crucial factor in the pathogenesis of intestinal I/R injury. Metformin, which is known to exhibit antiferroptotic properties, has elicited significant attention from both researchers and clinicians. This study was designed to comprehensively examine the protective effects of metformin against intestinal I/R injury and to elucidate the underlying potential mechanisms.MethodsTo achieve this goal, both in vivo and in vitro models of I/R injury were established. For the in vivo experiments, metformin was administered via intraperitoneal injection at the onset of reperfusion. ResultsThe results from HE staining in the in vivo model, along with IF staining of tight junction proteins in the in vitro model, clearly demonstrated that metformin effectively mitigated the damage to the intestinal barrier following I/R injury. Additionally, metformin was shown to improve ROS levels and mitochondrial function in the context of I/R injury. Moreover, metfornin was observed to reduce the formation of mitochondria‐associated membranes (MAMs), which is a process that is intricately linked to the onset of ferroptosis. Significantly, Western blot analysis of key ferroptosis-related proteins, including GPX4, FTH1 and SLC7A11, indicated that metformin inhibited ferroptosis.DiscussionIn conclusion, this study suggests that metformin exerts beneficial effects on intestinal I/R injury by suppressing MAM formation and ferroptosis, thereby highlighting its potential as a therapeutic agent for this challenging clinical condition.